Inheritance VS Intertemporal Consumption - Oktavia, Rina; M. Umar, Burhan; Asfi, Manzilati (Institute of Research and Community Service, University of Brawijaya, 2016)
There is a difference between the final goal of conventional economics and Islamic economics. This difference is about intertemporal consumption. In conventional economics, every human being trying to meet the needs through consumption activities. It is known as the term â€œintertemporal consumptionâ€. Intertemporal consumption is the consumption activities which are carried out in two periods, both present and future. Income (Y) obtained by a person is the sum of consumption (C) and savings (S) which is written in a mathematical function Y = C + S. However, in Islamic economics is known the term â€inheritanceâ€ which is the income of someone unused until someone dies thus distributed to the heirs. Thus, a person's income in Islamic economics is not just an accumulation of consumption (present and future) and savings, but also inheritance which is an instrument of wealth distribution to the heirs after death. This a literature study. And this research tries to explain the difference between inheritance as part of intertemporal consumption in Islamic economics perspective and intertemporal consumption in conventional economics perspective. From this research about inheritance and intertemporal consumption, we will know more clearly about the fundamental difference from conventional economics and Islamic economics.Keywords: Inheritance, Intertemporal Consumption, Islamic Economics, Conventional Economics